Blame the signaling: Role of cAMP for the resolution of inflammation (2020)
A complex intracellular signaling governs different cellular responses in inflammation. Extracellular stimuli are sensed, amplified, and transduced through a dynamic cellular network of messengers converting the first signal into a proper response: production of specific mediators, cell activation, survival, or death. Several overlapping pathways are coordinated to ensure specific and timely induction of inflammation to neutralize potential harms to the tissue. Ideally, the inflammatory response must be controlled and self-limited. Resolution of inflammation is an active process that culminates with termination of inflammation and restoration of tissue homeostasis. Comparably to the onset of inflammation, resolution responses are triggered by coordinated intracellular signaling pathways that transduce the message to the nucleus. However, the key messengers and pathways involved in signaling transduction for resolution are still poorly understood in comparison to the inflammatory network. cAMP has long been recognized as an inducer of anti-inflammatory responses and cAMP-dependent pathways have been extensively exploited pharmacologically to treat inflammatory diseases. Recently, cAMP has been pointed out as coordinator of key steps of resolution of inflammation. Here, we summarize the evidence for the role of cAMP at inducing important features of resolution of inflammation.